Gomco vs. plastibell office circumcision: No difference in overall post-procedural complications and healthcare utilization. Issue 1 (February 2021) - Nicassio, Lauren; Ching, Christina B.; Klamer, Brett; Sebastião, Yuri V.; Fuchs, Molly; McLeod, Daryl J.; Alpert, Seth; Jayanthi, Rama; DaJusta, Daniel
Summary: Introduction: Gomco clamp and Plastibell ring are common methods of office circumcision. While they possess similar features, the Plastibell is retained after the procedure which could impact perceived and true outcomes of the procedure. Objective: This study evaluated differences in complications, interventions, and healthcare utilization between Gomco and Plastibell office circumcision techniques. Study design: We retrospectively reviewed urology office performed circumcisions (January 2015–August 2018), limiting analysis to patients with follow-up. Patient demographics and circumcision technique were recorded. Complications, interventions, phone calls, emergency department (ED)/urgent care (UC) visits, and unplanned office visits directly related to the circumcision were recorded. Descriptive statistics for the number of patients experiencing an event and the number of days to event were summarized. Survival analysis with inverse probability of treatment weights was used to estimate hazard and incidence rate ratios (HR and IRR, respectively). Results: 746 patients were included for analysis. Median time of follow-up was 2.7 weeks (interquartile range 2–5). 257 (34%) patients underwent Gomco circumcision; 489 (66%) underwent Plastibell circumcision. The techniques did not significantly differ for complications (HR = 0.9, p = 0.497), interventions (HR = 0.89, p = 0.498), and hospital visits (HR = 1.0, p = 0.985) (Table ), although Plastibell patients presented to the ED/UC more (odds ratio = 1.6, p = 0.02). Plastibell patients generated proportionally more post-procedural phone calls (63 vs. 52%), though not significantly (IRR = 1.11; p = 0.426). Discussion: Overall, the type of device used for office circumcision, between Gomco clamp and Plastibell ring, does not appear to impact the outcome of circumcision. Providers should perform the method of office circumcision with which they are familiar and comfortable. There is an overall reliance on healthcare resources suggesting poor family preparation of the post-procedural course regardless of the technique, necessitating better patient education. Limitations of this study include its retrospective nature, variability in follow-up between techniques, and variety of providers, limited to pediatric urologists, performing circumcision. Conclusions: Gomco and Plastibell office circumcision techniques do not significantly differ in post-procedural complications, interventions, unplanned hospital visits, and office phone calls. Plastibell patients do present more often to the ED/UC perhaps as a result of increased anxiety and perceived immediacy of concerns with the device. Table Recurrent event Cox proportional hazard survival model results for complications, interventions, and unplanned hospital visits Table Event Predictor Level Hazard Ratio Lower CI Upper CI p-value Complication Technique Gomco Reference       Plastibell 0.9 0.67 1.21 0.497 Intervention Technique Gomco Reference       Plastibell 0.89 0.64 1.24 0.498 Unplanned hospital visit Technique Gomco Reference       Plastibell 1.0 0.66 1.53 0.985